Developing a point-of-care device for traumatic brain injury - Ifa Syafiqah Binte Sulaiman (Nanyang Technological University, 2022)
Traumatic Brain Injury (TBI) is an emerging worldwide issue which affects 69 million people worldwide. Currently, it is most prevalent in Southeast Asia and Western Pacific Region (18.3 million and 17.3 million respectively) mainly due to road traffic collisions caused by increased motorisation. Delayed diagnosis and treatment of TBI can lead to prolonged disabilities. However, diagnosing TBI efficiently remains a challenge due to the lack of a Point-of-Care (POC) product in emergency rooms, and current diagnostic methods may cause delays for patients to be diagnosed with TBI, detrimentally prolonging their disabilities. To address the unmet medical needs, this project aims to develop a POC product that can quickly detect two biomarkers of TBI, Glial Fibrillary Acidic Protein (GFAP) and Ubiquitin C–Terminus Hydrolase L1 (UCH-L1), in patient serum samples with a cutting-edge technology platform known as the Instant NanoBiosensors Fiber-Optic Particle Plasmon Resonance (INB FOPPR) System. Although further optimisation of protocols and experimental conditions are needed to achieve reproducibility with this system, INB FOPPR System gives promising results in meeting the medical needs of early TBI detection in a real-time manner, where there is an urgent demand for a POC product which can efficiently triage patients with TBI, especially in the emergency room.